2015
DOI: 10.1186/s12889-016-2720-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes in times of economic recession: a systematic literature review

Abstract: BackgroundCountries in recession experience high unemployment rates and a decline in living conditions, which, it has been suggested, negatively influences their populations’ health. The present review examines the recent evidence of the possible association between economic recessions and mental health outcomes.MethodsLiterature review of records identified through Medline, PsycINFO, SciELO, and EBSCO Host. Only original research papers, published between 2004 and 2014, peer-reviewed, non-qualitative research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
331
5
16

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 451 publications
(398 citation statements)
references
References 127 publications
(192 reference statements)
16
331
5
16
Order By: Relevance
“…Most prior work and syntheses of evidence, including US studies, have argued that working age men have been most adversely affected [15][16][17]. In contrast, we found that the only age-gender groups that demonstrated excess deaths due to the recession were men aged 65 and over and women aged 15-24 years.…”
Section: Discussioncontrasting
confidence: 53%
“…Most prior work and syntheses of evidence, including US studies, have argued that working age men have been most adversely affected [15][16][17]. In contrast, we found that the only age-gender groups that demonstrated excess deaths due to the recession were men aged 65 and over and women aged 15-24 years.…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, area level measures of housing markets are related to mental health; previous analyses found suicide rates increased with state‐level foreclosure rates (Houle & Light, ). Evidence from a review of 100 papers shows that unemployment, income decline, and debts had significant associations with poor self‐reported mental health, increased rates of common mental disorders, increases in substance use disorders, and suicidal behaviors in adults (Frasquilho et al, ). In these adult populations, no matter how mental health was measured, changes in business cycles are correlated with changes in mental health.…”
Section: Methodsmentioning
confidence: 99%
“…Economic disadvantages like unemployment, poverty, low education, and housing challenges are associated with increased risk of family conflict, social isolation, stress, and substance misuse. 1722 Concentrated economic disadvantage can contribute to collective frustration and hopelessness, 23 out-migration, community disinvestments, and social disorders like substance misuse. 23–30 Therefore, counties with greater economic, housing, and family distress should have higher drug-related mortality rates.…”
Section: Introductionmentioning
confidence: 99%